Mengelola Hubungan dengan Pelanggan pada Praktik Pemasaran Business to Business (B2B) dengan Orientasi Penciptaan Loyalitas - Audita Nuvriasari (Universitas Islam Indonesia, 2012)
The relationship between organization and their customers is a critical issue when establishing a long-term relationship. It is not only in Business to Customer (B2C) relationship but also in Business to Business (B2B). To maintenance the long-term relationship, the organization must create a customer loyalty in the business. The importance and benefits of attracting and maintaining loyal customers has arisen because there is a general acceptance that profitability follows customer loyalty. The objective of this research is to increase the understanding of managing and maintaining the relationship between customer and supplier in B2B marketing. Furthermore, the result of this research is to give some recommendations to create a customer loyalty in B2B marketing practice. Qualitative analysis is used in this research since it is the appropriate method to meet our purpose. In order to accomplish this research, one company in mattress industry (PT. Dinamika Indonusa Prima) has been used as an object. Some indicators to evaluate the practice of B2B marketing are: purpose of exchange, nature of communication, managerial intent, managerial focus, managerial investment, and managerial level. The result of this study indicate that the practice of B2B Marketing has done in a good practice and organization must meet the customer need in order to maintain customers and create a customer’s loyalty.Keywords: Business to Business (B2B) marketing, maintaining customer, customer’s loyalty